Pertanggungjawaban Pidana terhadap Pelaku pembuat Konten Perjudian Online Berbasis Live Streaming - Alhasani, Ahmad Ghifari; Ridwan, Ridwan; Rofiana, Reine (PAMPAS: Journal of Criminal Law, 2024)
This research aims to find out about live streaming-based online gambling content in criminal law and to find out the criminal liability of the perpetrators of live streaming-based online gambling content. This research method uses normative juridical research methods, with the research specifications used are the statutory approach, the news approach regarding online gambling and the case approach. The data source used is secondary data which consists of primary, secondary and tertiary legal materials, with literature study data collection techniques. The results of the research obtained are that online gambling content in criminal law is a criminal offense because it fulfills the elements of a criminal offense and there are regulations regarding gambling located in Articles 303 and 303bis of the Criminal Code, Article 426, Article 427 of Law No. 1 of 2023 and Article 27 paragraph (2) of the ITE Law. As for criminal liability regarding online gambling content creators, it is still arguably quite a few who can be held accountable. Abstrak Penelitian ini bertujuan untuk mengetahui mengenai konten perjudian online berbasis live streaming dalam hukum pidana serta untuk mengetahui pertanggungjawaban pidana pelaku pembuat konten perjudian online berbasis live streaming. Metode penelitian ini menggunakan metode penelitian yuridis normatif, dengan spesifikasi penelitian yang digunakan adalah pendekatan perundang-undangan, pendekatan berita mengenai perjudian online dan pendekatan kasus. Sumber data yang digunakan adalah data sekunder yang didalamnya terdiri dari bahan hukum primer, sekunder dan tersier, dengan Teknik pengumpulan data studi Pustaka. Hasil penelitian yang didapatkan yaitu konten perjudian online dalam hukum pidana termasuk tindak pidana karena memenuhi unsur-unsur tindak pidana dan ada peraturan tentang perjudian terletak pada Pasal 303 dan 303bis KUHP, Pasal 426, Pasal 427 UU No 1 Tahun 2023 dan Pasal 27 ayat (2) UU ITE. Sedangkan untuk  pertanggungjawaban pidana mengenai pembuat konten perjudian online ini masih dibilang cukup sedikit yang dapat dimintai pertanggungjawaban.